2018
DOI: 10.3389/fneur.2018.00555
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Vestibulopathy: Vestibular Function, Dynamic Visual Acuity and Functional Impact

Abstract: Introduction: Patients suffering from bilateral vestibular hypofunction (BVH) often experience ataxia as well as visual instability. Even though progress has been made in vestibular testing, insights regarding vestibular deficit in BVH remain incomplete since no method allows evaluation of frequency ranges of vestibular sensors in a continuous way. The aim of our study was to give a detailed description of the level of vestibular deficit in different ranges of vestibular stimulation and an exhaustive evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
3
18
0
2
Order By: Relevance
“…The observed fall prevalence in this study is comparable with previous studies evaluating falls in BV patients. Schniepp and colleagues reported falls in 21 out of 55 (39%) BV patients in the preceding six months [26], Hermann and colleagues reported falls in 11 out of 20 (55%) BV patients since the onset of BV [27]. Results will now be discussed in accordance with the four a priori hypotheses.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The observed fall prevalence in this study is comparable with previous studies evaluating falls in BV patients. Schniepp and colleagues reported falls in 21 out of 55 (39%) BV patients in the preceding six months [26], Hermann and colleagues reported falls in 11 out of 20 (55%) BV patients since the onset of BV [27]. Results will now be discussed in accordance with the four a priori hypotheses.…”
Section: Discussionmentioning
confidence: 65%
“…Significantly higher DHI scores, lower unipedal stance test, higher ataxia numeric scales and greater loss of upwards Dynamic Visual Acuity were observed in the patients with falls. Age was again not different between fallers and non-fallers [27]. On the contrary, Herdmann et al found a younger age to be a risk factor for falling [31].…”
Section: Risk Factors For Falls In Bv Patients According To Literaturementioning
confidence: 82%
See 1 more Smart Citation
“…Video HIT is the only tool that can also be used for the evaluation of vertical semi-circular canals [41]. Nevertheless, a disease-specific sparing of the anterior semi-circular canals has been highlighted in BVP rendering gain of the vertical canals a less reliable criterion [42,43].…”
Section: Vestibular Impairementmentioning
confidence: 99%
“…U ponad połowy chorych początkowe objawy mają lekki charakter. Z upływem czasu zwiększają się, prowadząc do znacznego pogorszenia komfortu życia [17][18][19]. Pogłębia się lęk przed zawrotami głowy, dlatego chorzy rezygnują z aktywności fizycznej, nierzadko izolując się od społeczeństwa i zamykając w domach.…”
Section: Omówienieunclassified